Pelatihan pemanfaatan buku panduan guru pada platform SIBI untuk MGMP Sejarah Kota Malang - Utami, Indah Wahyu Puji; Widiadi, Aditya Nugroho; Ayundasari, Lutfiah; Yuliati, Yuliati (Universitas Negeri Malang, 2025)
Abstract The implementation of the Merdeka Curriculum in Indonesia faces a number of challenges, especially among history teachers, including members of the Malang City History MGMP. One of the problems that needs to be addressed immediately is the curriculum change that will be implemented starting July 2024. Most teachers are still confused about curriculum operations, especially in implementing the curriculum in schools (enacted curriculum). As a solution, we carry out technical guidance activities for utilizing the Teacher's Manual (BG) on the SIBI platform. The History BG, compiled by experts, contains suggestions for curriculum operationalization as well as alternative resources to improve teachers' understanding of essential materials. This community service activity includes preparation, implementation, and evaluation, held at the SMAN 1 Malang Hall, involving 30 Malang City History MGMP teachers. The material presented included new perspectives on the Merdeka Curriculum, essential material mapping, and technical guidance on the use of the SIBI and BG History platforms. Based on a survey conducted at the end of the meeting, this activity was found to increase the readiness and competence of Malang City History MGMP members in dealing with curriculum changes. Abstrak Pelaksanaan Kurikulum Merdeka di Indonesia menghadapi sejumlah tantangan, khususnya di kalangan guru sejarah, termasuk anggota MGMP Sejarah Kota Malang. Salah satu masalah yang perlu untuk segera ditangani adalah perubahan kurikulum yang diterapkan mulai Juli 2024. Sebagian besar guru masih bingung dengan operasional kurikulum, terutama dalam pelaksanaan kurikulum di sekolah (enacted curriculum). Sebagai solusi, kami melaksanakan kegiatan bimbingan teknis pemanfaatan Buku Panduan Guru (BG) di platform SIBI. BG Sejarah, yang disusun oleh para ahli, berisi saran untuk operasionalisasi kurikulum serta sumber alternatif untuk meningkatkan pemahaman guru terhadap materi esensial. Kegiatan pengabdian kepada masyarakat ini meliputi persiapan, pelaksanaan, dan evaluasi, diadakan di Aula SMAN 1 Malang, dengan melibatkan 30 guru MGMP Sejarah Kota Malang. Materi yang disampaikan mencakup perspektif baru Kurikulum Merdeka, pemetaan materi esensial, serta bimbingan teknis penggunaan platform SIBI dan BG Sejarah. Berdasarkan survey yang dilakukan pada akhir pertemuan, kegiatan ini ternyata meningkatkan kesiapan dan kompetensi anggota MGMP Sejarah Kota Malang dalam menghadapi perubahan kurikulum.